La literatura infantil y juvenil como estrategia didáctica para desarrollar la macrodestreza de leer en el décimo grado de educación básica superior, de la unidad educativa Adolfo Valarezo, de la ciudad de Loja, año lectivo 2016-2017. - Jimenez Abarca, Glenda Andrea (2017)
In the present research work entitled: LA CHILDREN'S LITERATURE AS A TEACHING STRATEGY TO DEVELOP MACRODESTREZA READ IN TENTH GRADE TOP BASIC EDUCATION EDUCATION UNIT ADOLFO VALAREZO, LOJA CITY, SCHOOL YEAR 2016-2017 It was proposed as a general objective: to analyze the importance of applying Child and Youth Literature as a didactic strategy to develop the macrodestreza of reading in the tenth grade of Higher Basic Education, of the school investigated. For its development the following methods were used: scientific, descriptive, analytical-synthetic and inductive-deductive, which contributed throughout the research process. The techniques used were the bibliographical, the interview that was addressed to the teachers and the survey applied to the students; And the instruments that were used were the interview guide structure and the questionnaire. Through the use of techniques and instruments it was possible to know the following results, in conclusion in the Educational Unit object of study, Children's and Juvenile Literature is used, however, this is not directed to serve as didactic strategy, Both teachers and students are unaware of their pedagogical benefits, so it is recommended that teachers implement a corpus of child and youth literature methodologically supported to encourage students to read this type of text.